WORK BRICKWORK CRACKS IN THE TRANSFORMED INTERNAL VALVES ELEMENT - and and (Municipal economy of cities. Series: «Economy science», 2013)
It was identified stress state of masonry reinforced with basalt-plastic in the crack zone.